Usefulness of a New Device to Monitor Cerebral Blood Oxygenation Using NIRS During Cardiopulmonary Resuscitation in Patients with Cardiac Arrest: A Pilot Study - Yagi, Tsukasa; Kawamorita, Tsuyoshi; Kuronuma, Keiichiro; Tachibana, Eizo; Watanabe, Kazuhiro; Chiba, Nobutaka; Ashida, Tadashi; Atsumi, Wataru; Kunimoto, Satoshi; Tani, Shigemasa; Matsumoto, Naoya; Okumura, Yasuo; et al. (Advances in experimental medicine and biology, 2020)
Recent guidelines on cardiopulmonary resuscitation (CPR) have stressed the necessity to improve the quality of CPR. Our previous studies demonstrated the usefulness of monitoring cerebral blood oxygenation (CBO) during CPR by near-infrared spectroscopy (NIRS). The present study evaluates whether the NIRO-CCR1, a new NIRS device, is as useful in the clinical setting as the NIRO-200NX. We monitored CBO in 20 patients with cardiac arrest by NIRS. On the arrival of patients at the emergency department, the attending physician immediately assessed whether the patient was eligible for this study after conventional advanced life support and, if eligible, measured CBO in the frontal lobe by NIRS. We found that in all patients, the cerebral blood flow waveform was in synchrony with the chest compressions. Moreover, the tissue oxygenation index increased following cardiopulmonary bypass (CPB) in patients undergoing CPB, including one patient in whom CBO was monitored using the NIRO-CCR1. In addition, although the NIRO-CCR1 could display the pulse rate (Tempo) in real time, Tempo was not always detected, despite detection of the cerebral blood flow waveform. This suggested that chest compressions may not have been effective, indicating that the NIRO-CCR1 also seems useful to assess the quality of CPR. This study suggests that the NIRO-CCR1 can measure CBO during CPR in patients with cardiac arrest as effectively as the NIRO-200NX; in addition, the new NIRO-CCR1 may be even more useful, especially in prehospital fields (e.g. in an ambulance), since it is easy to carry.